2004
DOI: 10.1242/dev.01095
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila parkinmutants have decreased mass and cell size and increased sensitivity to oxygen radical stress

Abstract: third larval instar stage, suggesting that larval musculature is intact and that parkin is required only in pupal and adult muscle. parkin flies do not show an age-dependent dopaminergic neuron loss in the brain, even after aging adults for 3 weeks. Nevertheless, degeneration of IFMs demonstrates the importance of parkin in maintaining specific cell groups, perhaps those with a high-energy demand and the concomitant production of high levels of free radicals. parkin mutants will be a valuable model for future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
354
2
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(386 citation statements)
references
References 71 publications
21
354
2
6
Order By: Relevance
“…The loss of parkin in Drosophila successfully recapitulated human PD symptoms such as movement disorders and DA neuron degeneration (Cha et al, 2005;Greene et al, 2003;Pesah et al, 2004). Moreover, L-DOPA substantially rescued the reduced climbing ability of parkin mutants, confirming that Drosophila parkin mutant models accurately simulate human PD patients (Cha et al, 2005).…”
Section: Parkin Protects Mitochondria Downstream Of Pink1mentioning
confidence: 66%
“…The loss of parkin in Drosophila successfully recapitulated human PD symptoms such as movement disorders and DA neuron degeneration (Cha et al, 2005;Greene et al, 2003;Pesah et al, 2004). Moreover, L-DOPA substantially rescued the reduced climbing ability of parkin mutants, confirming that Drosophila parkin mutant models accurately simulate human PD patients (Cha et al, 2005).…”
Section: Parkin Protects Mitochondria Downstream Of Pink1mentioning
confidence: 66%
“…In PD, identification of disease-specific genes that influence mitochondrial physiology, either directly or indirectly, have contributed greatly to our understanding of the role of mitochondrial impairment in the etiology of this disease [1,2]. For example, mitochondrial pathology and oxidative stress are prominent in Drosophila parkin null mutants, and are associated with degeneration of a subset of dopaminergic neurons in the brain [11,60,61]. Although nigral degeneration is absent in parkin-deficient mice, they exhibit decreased striatal mitochondrial respiratory capacity and decreased levels of proteins involved in protection from oxidative stress [12].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in mitochondrial morphologyhave been also observed, but this led only to disruption of complex I function in nigral mitochondria and did not result in cell death [233]. Thus, mitochondrial defects and an increased susceptibility to oxygen radical damage were also reported in a parkin knockout model of Drosophila, suggesting that abnormalities in parkin ubiquitination function might be secondary in the course of pathogenic events [234,235]. In vitro studies of PARK2Ͳknockdown SHͲSY5Y neuroblastoma cell line showed apoptotic cell death and high levels of autoxidized forms of LͲ DOPA and dopamine, suggesting that parkin might have important antioxidant properties [236].…”
Section: Parkinmentioning
confidence: 99%